On the Road to Precision Medicine: Magnetic Systems for Tissue Regeneration, Drug Delivery, Imaging, and Theranostics - Francesca Garello; Yulia Svenskaya; Bogdan Parakhonskiy; Miriam Filippi (MDPI AG, 2023)
Magnetic systems have always been considered as attractive due to their remarkable versatility [...]